Novel Application of Photo-Crosslinked Urocanic-Acid-Modified Chitosan in Corneal Wounds - Lee, An Li; Hsieh, Hao Ying; Chen, Yun Yu; Tsai, Li Hui; Wey, Shiuan Li; Chen, Daishi; Chen, Yi Jane; Young, Tai Horng (ACS Biomaterials Science and Engineering, 2022)
In the last few years, the use of tissue adhesives in corneal perforation has gained immense popularity in clinical practices. The present study aimed to devise a new application of urocanic-acid-modified chitosan (CS) with methylene blue (MB) as a photosensitizer for the development of a photo-crosslinked tissue adhesive. In particular, the curing time was controlled with the aid of a 650 nm red diode. Under the same irradiation condition, the mechanical properties were tuned using the photosensitizer at different concentrations. In vitro tests revealed that the gel was ductile and biocompatible. The application of the gel to a perforated cornea model stopped the leakage of aqueous humor, immediately after the gel was photo-crosslinked. The blue appearance of the gel provided high precision when applied to corneal wounds. Importantly, the crosslinked gel became transparent within 24 h, owing to the dissipation of MB from tears, and the gel spontaneously sloughed off without artificial removal. Altogether, the study reported the development of a novel photo-crosslinkable urocanic-acid-modified CS gel that exhibited significant potential to be utilized in the healing of corneal perforation.
CRIS-Team Scopus Importer:2022-05-13
Keywords: bioadhesive; hydrogel; ophthalmic injury; photochemical; tissue glue; wound healing